The influence of near service environmental conditions on the corrosion and LCF behaviour of a beta-stabilized γ-TiAl alloy - Löffl, Christian; Saage, Holger; Göken, Mathias (Corrosion Science, 2020)
The damage behaviour of the TiAl alloy Ti-43.5Al-4Nb-1Mo-0.1B was investigated by isothermal thermogravimetric-analysis (TGA) and strain controlled low-cycle-fatigue (LCF) experiments at high temperature. Aluminium depletion and the formation of a continuous brittle layer in the subsurface zone takes place in synthetic exhaust gas. Contrary, a continuous ductile γ-phase forms in the subsurface zone in air. Since a continuous TiN layer as diffusion barrier is not formed in the early stages of corrosion, strong hardening is observed in LCF test samples in exhaust gas and a strain amplitude of 0,6 %, leading to a significant reduction of the cycles to failure.
CRIS-Team Scopus Importer:2020-08-07
Keywords: corrosion fatigue; environmental effects; high temperature corrosion; titanium aluminides